The Role of East Java Bawaslu in Increasing Participatory Supervision in the 2024 East Java Regional Election - Anugrah, Rangga Wahyu; Muljanto, Muhammad Agus (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
Democracy is a system of government that places the people at the center of decision-making, with General Elections (Pemilu) as the main mechanism for electing leaders and representatives of the people. Fair, honest, and transparent elections rely heavily on the role of election organizers, especially the Election Supervisory Body (Bawaslu). However, unhealthy political practices, such as money politics and fraud, often undermine the integrity of elections and democracy itself. This study aims to examine Bawaslu's role in election supervision and the importance of community participation in ensuring the success of clean and fair elections. The results show that although Bawaslu has a strategic role in supervision, limited human resources and the vast territory of Indonesia require active community participation. Participatory supervision is the key to narrowing the space for violations and increasing transparency and accountability of elections. In conclusion, public participation in election supervision strengthens the democratic system and ensures the implementation of fairer, honest and transparent elections, thereby reducing the possibility of political manipulation that harms people's sovereignty.